Jean Jaurès : his life and work - Jackson, John Hampden (London : George Allen & Unwin, 1943)
Bibliotheek Camille Huysmans
Dedicator: Renner, Karl, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: Jaurès, Jean